A New Graphical Password System Using Intersecting Points in a Signature - Yang, Gi-Chul; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: These days the most commonly used method of digital user authentication uses text-basedÂ passwords. Security enhancements using text-basedÂ passwordsrequire long and complex passwords, but long and complex text-based passwords are hard to remember and inconvenient to use. Therefore, authentication techniques that can replace text-based passwords are necessary. The objective of this paper is developing a user friendly graphical password system with strong security power.Methods/Statistical analysis: In order to develop a user friendly graphical password system with strong security power, the system developed in this articlecalled PassSign adapts advantages fromthe PassPositions system and signature recognition system. PassPositions system usie relative position information of click points and it is a recognition error free system with high usability. Signature recognition system has strong security power since it is hard to redraw someone elseâ€™s signature but error prone. PassSign takes signatures as passwords and use relative position information of intersecting points generated in an input signature to identify a certain userâ€™s signature for high usability andstrong security.Findings: There are various existing graphical password systems with there own advantages and disadvantages. Among the existing graphical password systems, signature recognition system has advantages of usability and strong security. It is, however, expensive to implement and error prone. PassPositions system also has advantages of reliability and usability, but has not good enough password space. PassSign system developed in this article removes all the disadvantages of those systems while all the advantages are remain.Improvements/Applications: This article introduces a new graphical password system called PassSign. PassSign took advantages of existing graphical password systems and it is user friendly and recognition free with strong security power. Also, PassSign is a light and inexpensive user authentication system which is suitable for various mobile devices with relatively small memory space.Â Â